Construction of turmerone motif-fused spiropyrrolidine oxindoles and their biological evaluation for anticancer activities. Issue 12 (23rd March 2016) - Liu, Xiong-Li; Yang, Chao; Zhang, Wen-Hui; Zhou, Gen; Ma, Xi-Tao; Lin, Bing; Zhang, Min; Zhou, Ying; Feng, Ting-Ting
Graphical abstract: Highlights: An expedient method toward the synthesis of novel turmerone fused spiropyrrolidine oxindoles was developed. Products bearing adjacent quaternary–tertiary centers were obtained in high yields along with good diastereoselectivity. Promising activities against K562 and A549 cell lines have been demonstrated. The results show the potential candidates for exploring new drug-like molecules. Abstract: Developed herein is a facile and efficient methodology toward the synthesis of novel turmerone motif-fused spiropyrrolidine oxindoles via a multicomponent 1, 3-dipolar cycloaddition event of dienones2 with azomethine ylides (thermally generated in situ from isatin derivatives and sarcosine). Products bearing adjacent quaternary–tertiary centers were smoothly obtained in high yields (up to 93% yield) with good diastereoselectivity (up to >20:1). In addition, their biological activity has been preliminarily demonstrated by in vitro evaluation against human lung cancer cells A549 and human leukemia cells K562 by the MTT-based assays, using the commercially available standard drug of Cisplatin as a positive control. The results also demonstrated that most of the compounds showed considerable cytotoxicities to these two cell lines of K562 and A549, showed comparably potent or even more potent than the positive control of Cisplatin (up to 5.1 times), and indicated that novel turmerone motif-fused spiropyrrolidine oxindoles may be potential leads for further biological screenings and may generate drug-like molecules.